Records Keeping on Financial Performance of Small and Medium Enterprises in Industrial City Division, Mbale City - Racheal Muyama (Uganda Christian University, 2025)
This research study sought to investigate records Keeping and financial performance of small and medium enterprises in Industrial city division, Mbale city and the literature is reviewed according to the three objectives which include; to examine the effect of cash book on financial performance of small and medium enterprises in Industrial city division, to establish the effect of ledgers on financial performance of small and medium enterprises in Industrial city division, to analyze the effect of journals on financial performance of small and medium enterprises in Industrial city division and chapter summery. The study used a sample size of 63 respondents, it also used questionnaires to collect data that is closed ended questionnaires. The results of the first objective showed that cash book has a significant effect on financial performance of small and medium enterprises in industrial city division. Majority of the respondents; 54% of respondents (30% strongly agree, 24% agree) confirmed that cashbooks provide accurate daily records of inflows and outflows, which improves liquidity Keeping and decision-making. Similarly, 62% agreed that accurate entries help detect cash shortages early and prevent financial losses. Additionally, 61% of respondents noted that regular updates of cashbooks support effective budgeting and financial planning. Results of second objective showed that ledgers have a significant effect on financial performance of small and medium enterprises in industrial city division. The majority, 80% of respondents (33% strongly agree, 47% agree), stated that proper ledger maintenance ensures accuracy in accounts and increases reliability in financial reporting. In addition, 57% agreed that organized ledgers enable SMEs to identify profitable and loss-making activities, thereby supporting resource allocation. Results of the third objective indicated that journals have a significant effect on financial performance of small and medium enterprises in industrial city division. A majority, 62% (38% strongly agree, 24% agree), indicated that recording transactions in journals prevents omission of data, thereby enhancing financial integrity. There is need for the government to support SMEs in improving cashbook Keeping to enhance their financial performance. Policies that encourage the adoption of digital accounting tools can help reduce errors and increase efficiency. Subsidies or grants for acquiring accounting software make it easier for SMEs to modernize their record-keeping. Training programs and workshops organized by government agencies can improve the bookkeeping skills of SME owners and employees. Regulatory frameworks should enforce proper financial reporting standards to ensure transparency.